2019
DOI: 10.1590/1806-9282.65.6.801
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and anxiety and their association with cardiovascular risk factors in Northeast Brasil primary care patients

Abstract: SUMMARY BACKGROUND: Depression and anxiety disorders (DAD) are the most prevalent mental health conditions worldwide. Among the adult population served in basic care, it is estimated that depression affects about 14.3% of these individuals worldwide, and between 21.4% and 31% in Brasil. Anxiety affects up to 33.7% of the population during their lifetimes. OBJECTIVES: estimate the prevalence proportions of DAD among patients in a municipality in Northeast Brasil and study the association between DAD and cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
(28 reference statements)
0
3
1
Order By: Relevance
“…The prevalence in this study was relatively higher than the studies reported from Saudi Arabia, Iran, India, United Kingdom, Northeast Brazil, South Brazil, Uganda, and Nigeria which was 25.5%, 34.8%, 44.1%, 8.1%, 27.1%, 33.7%, 22.5%, and 22% respectively [22][23][24][25][26][27][28][29] and similarly higher than the studies reported from Vietnam, Jazan Province of Saudi Arabia, Southern Taiwan, Hawassa, Ethiopia, Amanuel mental health hospital, Ethiopia, Menelik II hospital, Ethiopia which was 5.4%, 20.6%,38%, 22.1%, 27.1%, and 23.2% respectively. 5,[30][31][32][33][34] This variation might have resulted from a methodological difference or study population, where data were taken from chronic medical-surgical and trauma inpatients including intensive care unit inpatients, difference in screening and diagnostic questionnaire tool used; some researchers used Kessler scale, Burden Assessment Scale, Hospital Depression, Anxiety and Stress Scale to measure mental distress and other sociodemographic and environmental factors may have increased the prevalence of mental distress in this study.…”
Section: Prevalence Of Mental Distresscontrasting
confidence: 73%
“…The prevalence in this study was relatively higher than the studies reported from Saudi Arabia, Iran, India, United Kingdom, Northeast Brazil, South Brazil, Uganda, and Nigeria which was 25.5%, 34.8%, 44.1%, 8.1%, 27.1%, 33.7%, 22.5%, and 22% respectively [22][23][24][25][26][27][28][29] and similarly higher than the studies reported from Vietnam, Jazan Province of Saudi Arabia, Southern Taiwan, Hawassa, Ethiopia, Amanuel mental health hospital, Ethiopia, Menelik II hospital, Ethiopia which was 5.4%, 20.6%,38%, 22.1%, 27.1%, and 23.2% respectively. 5,[30][31][32][33][34] This variation might have resulted from a methodological difference or study population, where data were taken from chronic medical-surgical and trauma inpatients including intensive care unit inpatients, difference in screening and diagnostic questionnaire tool used; some researchers used Kessler scale, Burden Assessment Scale, Hospital Depression, Anxiety and Stress Scale to measure mental distress and other sociodemographic and environmental factors may have increased the prevalence of mental distress in this study.…”
Section: Prevalence Of Mental Distresscontrasting
confidence: 73%
“…It has 7 items related to anxiety and 7 other items related to depression [18]. The score category is the sum of all the answers, namely no symptoms (score 0-7), mild (score 8-10), moderate (score [11][12][13][14] and severe (score [15][16][17][18][19][20][21].We used the therapeutic communication observation form adapted from Lukmanulhakim et al [14]. It consists of 20 statements made based on the content of therapeutic communication interventions with "yes" and "no" answer choices.…”
Section: Methodsmentioning
confidence: 99%
“…Arterial hypertension, obesity and hyperlipidemia are the three factors associated significantly with Depression Anxiety Disorder (DAD) [12]. Cardiac rehabilitation using pharmacological and non-pharmacological therapies is an important step to improve the patients' condition.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with hypertension were more likely to suffer from mental illnesses, such as anxiety disorders. In Afghanistan, anxiety accounted for 42.3% of hypertension patients, while Northeastern Brazil revealed that symptoms of anxiety and hypertension were present in 27.1% of patients [2], [3]. There is currently a dearth of research on anxiety in hypertension patients, especially in Can Tho City and Can Tho Traditional Medicine Hospital.…”
Section: Introductionmentioning
confidence: 99%